Antinociceptive and anti-inflammatory activities of Dicranopteris linearis leaves chloroform extract in experimental animals - Zakaria, Zainul Amiruddin; Abdul Ghani, Zuleen Delina Fasya; Raden Mohd Nor, Raden Nur Suraya; Gopalan, Hanan Kumar; Sulaiman, Mohd Roslan; Abdullah, Fatimah Corazon (The Pharmaceutical Society of Japan, 2006)
The present study was carried out to establish the antinociceptive and anti-inflammatory properties of Dicranopteris linearis leaves chloroform extract in experimental animals. The antinociceptive activity was measured using the abdominal constriction, formalin and hot plate tests, while the anti-inflammatory activity was measured using the carrageenan-induced paw edema. The extract, obtained after 72 h soaking of the air-dried leaves in chloroform followed by evaporation under vacuo (40°C) to dryness, was dissolved in dimethyl sulfoxide to the doses of 20, 100 and 200 mg/kg and administered subcutaneously 30 min prior to subjection to the above mentioned assays. The extract, at all doses used, was found to exhibit significant (p<0.05) antinociceptive activity in a dose-dependent manner. However, the significant (p<0.05) anti-inflammatory activity observed occur in a dose-independent manner. As a conclusion, the chloroform extract of D. linearis possesses antinociceptive and anti-inflammatory activity and thus justify its traditional uses by the Malays to treat various ailments.